Developing Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence in Secondary School Level Students - Haziratul Qudsiyah; Fathurrahman Muhtar (CV. Creative Tugu Pena, 2024)
Intelligence is the perfection of the development of the mind, intelligence is also said to be a person's ability to solve problems faced and demands the ability of the mind. This research aims to determine the development of intellectual intelligence, emotional intelligence and spiritual intelligence of secondary school students. The research results show that intellectual intelligence is the human ability to absorb things that are phenomenally factual, the human ability to respond to the universe. Emotional intelligence is the human ability to motivate oneself and others, recognize one's own feelings and in dealing with other people, the ability to empathize and sympathize with others. Spiritual intelligence is intelligence that is used to face and solve problems of meaning and value, as well as placing our behavior and life in a broader and richer context of meaning and assessing that one's actions and way of life are more meaningful than others.